Worship, veneration, and idolatry: observations from C. S. Lewis. Issue 4 (December 2015) - LEPOJÄRVI, JASON
Abstract What does it mean to love God 'more' than people? This article engages the difficulty of defining worship, veneration, and idolatry, by looking at C. S. Lewis's observations on the subject. Lewis offers helpful nudges towards more than a merely conceptual distinction, but he does not consistently apply his love principles to cover human love for the saints (Mary in particular). The article concludes with eight follow-up questions that benefit philosophers and theologians alike as they seek to formulate more focused definitions of worship, veneration, and idolatry.